Sociodemographic correlates of perceived physical literacy in Spanish adolescents: results from the EHDLA study - María Mendoza-Muñoz; José Francisco López-Gil; José Francisco López-Gil; Damián Pereira-Payo; Raquel Pastor-Cisneros (Frontiers in Sports and Active Living, 2025)
Background/ObjectivePerceived physical literacy (PPL) is a crucial factor influencing adolescents’ engagement in physical activity and overall well-being. This study tried to determine the sociodemographic correlates of PPL among adolescents in Spain.MethodsA total of 1,378 participants [51% girls, median age = 14 years, interquartile range (IQR) 13 to 16] were analyzed. PPL was assessed via the Spanish Perceived Physical Literacy Scale (S-PPLL), with a median score of 33.0 (IQR 30.0 to 37.0). A generalized linear model was carried out to determine the correlates associated with a higher PPL.ResultsThe model revealed significant associations between sex, SES, and maternal education with PPL. Compared with boys, girls presented a lower association with PPL [unstandardized beta coefficient [B] = −1.24, 95% confidence interval [CI] −1.93 to −0.55, p < 0.001]. A higher SES was positively associated with greater PPL (medium SES: B = 1.76, 95% CI 0.81 to 2.70, p < 0.001; high SES: B = 2.34, 95% CI 1.22 to 3.45, p < 0.001), in comparison with those with lower SES. Additionally, maternal education level was positively associated with adolescents’ PPL scores, with higher education levels linked to greater PPL (B = 1.48, 95% CI 0.41 to 2.55, p = 0.007). However, factors such as immigrant status, paternal education, family structure, number of siblings, type of schooling, and area of residence were not significantly associated with PPL (p > 0.05).ConclusionSex, SES, and maternal education could influence adolescents’ PPL, highlighting the need for targeted interventions to address disparities and promote PL.